THE INFLUENCE OF STUDENTS’ ATTITUDE AND PERCEPTION ON SCIENTIFIC APPROACH TOWARD THEIR ENGLISH ACHIEVEMENT AT SMA MUHAMMADIYAH 11 PADANGSIDIMPUAN - Simamora, Diena Fitria (Journal of Education and Teaching, 2021)
The purpose of this study was found out the influence of Students’ Attitude and Perception on Implementing the Scientific Approach Toward their English Achievement at SMA Muhammadiyah 11 Padangsidimpuan. This study was a correlational research design of expo facto using two independent variables and one dependent variable, Students’ attitude (X1) and Perception (X2) were independent variables, and English achievement (Y) as dependent variable. Three research questions were stated in this research. There were 41 respondents of the eleventh grade students of SMA Muhammadiyah 11 Padangsidimpuan. Total sampling was used in this research because the number of students was not so many. Data of students’ attitude and perception were collected using questionnaires of Likert’s scale, while the students’ achievement was taken from a documented data. The data were analysed by using Product-Moment formula and the analysis of variance for multiple regressions data. Three hypotheses were stated in this research. The result of the first hypothesis is showed that students’ attitude toward English achievement had more significant influence compared to the second hypothesis of the influence of the students’ perception through scientific approach on students’ English achievement. At last, the finding can be concluded that there were significant influences of students’ attitude and perception toward the English achievement of the students at SMA Muhammadiyah 11 Padangsidimpuan. Keyword: Students’ attitude, perception, scientific approach, English achievement.